2014
DOI: 10.1590/1677-3225v13n2a02
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial microleakage at the implant-abutment interface in Morse taper implants

Abstract: Aim: To evaluate the microleakage at the implant-abutment (I-A) interface of Morse tapered implants inoculated with different volumes of bacterial suspension. Methods: Morse tapered I-A sets were selected and divided in two groups depending on the type of abutment: passing screw (PS) and solid (S), and then subdivided into four subgroups (n=6) according to the suspension volume: PS1: 0.1 µL; PS3: 0.3 µL; PS5: 0.5 µL; PS7: 0.7 µL; S1: 0.1 µL; S3: 0.3 µL; S5: 0.5 µL and S7: 0.7 µL. A control test was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Frequent failures in dental implants therapy are related to lack of stability or misfit at the implantabutment interface (5). Indeed, micro-gap on the interface of two-piece implants with variable fluid flow at this interface (6,7) leads to the occurrence of bacterial infiltration and inflammatory cells that result in bone loss around this area (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent failures in dental implants therapy are related to lack of stability or misfit at the implantabutment interface (5). Indeed, micro-gap on the interface of two-piece implants with variable fluid flow at this interface (6,7) leads to the occurrence of bacterial infiltration and inflammatory cells that result in bone loss around this area (8).…”
Section: Introductionmentioning
confidence: 99%
“…Such complication leads to studies on reduction of bacterial penetration by increasing the accuracy and stability of the jointed pieces through fabricating very high precision mechanical parts. Internal conical joints have superior mechanical stability of the I-A interface and have revealed no crest bone loss (5,16). This has been explained by the stress distribution of the implant's long axis through function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, surface oxide layers break down, a phenomenon known as cold welding 11 . Therefore, there is less risk of gaps between the implant and abutment, producing a seal proven to delay or even prevent bacterial invasion [12][13][14] and to be clinically reliable 15 . A recent study on implant components stability demonstrated that loosening in sets with internal tapered connections is less frequent than in sets with other connection types 16 .…”
Section: Introductionmentioning
confidence: 99%